Comparative Histological Changes to Investigate the Therapeutic Effect of Cicalfate+ cream and Penicillin-Streptomycin on Wound Healing in Rabbits - Hayder Nadhim Alkhalissi (Academic International Journal of Pure Science, 2025)
The present study was designed to evaluate the comparative effect of Cicalfate+ cream and penicillin-streptomycin on the histology of rabbits’ healing processes in full-thickness skin wounds. All rabbits were forty-five healthy adult bucks weighing between 1.3 and 1.8 kg were made A full-thickness wound measuring 2.5 x 2.5 cm was made in the dorsal back area. Intramuscular injections of xylazine hydrochloride (5 mg/kg), ketamine hydrochloride (35 mg/kg) were given very quickly (IM), along with 1 mg/kg of diazepam. These animals were separated into three groups (A, B and C groups) The first group was treated intramuscular with penicillin-streptomycin daily with single dose (group A), and the second group was given Cicalfate+ cream topically twice daily (group B), the last group designated as (group C) served as the control and didn’t receive any treatment. For histopathological evaluation, on the 3rd, 7th, and 14th days after wounding. Histological analysis demonstrated that wound healing was more organized and efficient in group (B) compared to the other groups, with group (A) showing a moderate degree of improvement, and the rate of healing highly in group (B) than other groups which led to highly attachment between layers of skin resulting in good blood supply and nutrition also greater cellularity and finally faster healing to the wound.